FORMING A QUALITY MANAGEMENT SYSTEM IN ENTERPRISES UNDER CONDITIONS OF ECONOMIC MODERNIZATION - Rakhimova Dilrabo Oktyabrovna; Doniyarov Dostonbek Rustam o'g'li (Proximus Journal Publishing, 2025)
This article covers the theoretical foundations of quality management, the concept of quality and its developmental stages, international standards, and modern management principles. Within the scope of the article, detailed information is provided on the basic principles of quality management, international experiences, and the theoretical aspects of the quality management system in the national economy. The possibilities of enhancing the competitiveness of enterprises through the effective organization of a quality management system are explored
Keywords: quality management; theoretical foundations; ISO standards